An inter-alia analysis on leverage and stock returns between diversified and undiversified firms in Malaysia / Munira Saera Zainal Abidin - Zainal Abidin, Munira Saera (2017)
This paper aims to investigate the evidence of using leverage ratio are able to determine the stock return of the company listed in Malaysia based on their category mainly as undiversified and diversified firm. Three variables are used as control variables in explaining the stock return which are Debt to Equity Ratio (DER), Long Term Debt Ratio (LTD) and Interest Coverage Ratio (ICR). This sample study covers the period of 2011 until 2015 using annually data for listed companies in Main Board of Bursa Malaysia from different industry. Results from the multiple regressions analysis show that all variables such as DER, LTD and ICR are moves opposite from the stock return. However, the result for diversified firm in large company shows that DER has a positive relationship with the stock returns. On the other hand, the result indicates that there is no significant relationship between those variables namely DER, LTD and ICR with the stock return between diversified and undiversified firm in Malaysia.